Оцінки “трудового принципу” Директорії УНР у сучасній вітчизняній історіографії - Лейберов, О. (Інститут історії України НАН України, 2008)
The article is devoted to the main ideological and political ends of establishment and functioning of the Directory of UNR. The author analyses in detail the national-state model which was based on the “working principle”. The special attention is devoted to the problems of authorship, appearance, and functioning, the reasons of the liquidation of model of the “working democracy” in the monographs and articles of native historians.